2021
DOI: 10.1111/ffe.13451
|View full text |Cite
|
Sign up to set email alerts
|

A microstructure‐based homogenization model for predicting the low‐cycle fatigue initiation life of GH4169 superalloy

Abstract: A microstructure-based homogenization model is proposed for simulating the cyclic plasticity and predicting the low-cycle fatigue (LCF) crack initiation life of GH4169 superalloy. Classical crystal plastic model (CPM) with a simple softening model is used at the grain level. Then, the transition from grain level to polycrystal level is based on the conservation of virtual work between the two levels. The Eshelby's formulation is applied in the model. Especially, local influences of grain interactions are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The parameters related to the fatigue damage model are determined using strain‐controlled LCF test data. The parameters related to the creep damage model are determined using the creep test data of Inconel 718 by Wang et al 20 In addition, to validate the applicability of the proposed life prediction method for different materials, this paper uses three material parameters for verification: nickel‐based superalloy Inconel 718, 19 martensitic heat‐resistant steel P92, 21,37,38 and stainless steel 316L 39 . The method of calculating the parameters of the CDM model used in the life prediction model has been described in detail in previous papers 40 .…”
Section: Life Prediction Model and Damage Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters related to the fatigue damage model are determined using strain‐controlled LCF test data. The parameters related to the creep damage model are determined using the creep test data of Inconel 718 by Wang et al 20 In addition, to validate the applicability of the proposed life prediction method for different materials, this paper uses three material parameters for verification: nickel‐based superalloy Inconel 718, 19 martensitic heat‐resistant steel P92, 21,37,38 and stainless steel 316L 39 . The method of calculating the parameters of the CDM model used in the life prediction model has been described in detail in previous papers 40 .…”
Section: Life Prediction Model and Damage Assessmentmentioning
confidence: 99%
“…After obtaining the basic deformation response of the material, many scholars have proposed various models to accurately predict the service life of the material. [14][15][16][17] Praveen and Yang et al 18,19 investigated the deformation response and damage mechanism of Inconel 718 under LCF loading and predicted the fatigue life and found that the material exhibits cyclic softening characteristics under LCF loading. Chen and Wang et al 16,20 investigated the deformation behavior and damage mechanism of Inconel 718 under conventional strain-controlled creep-fatigue interaction (CCFI) loading and found that the creep-fatigue life saturates with increasing dwell time.…”
Section: Introductionmentioning
confidence: 99%
“…The scatter fatigue life of UFG AA6061 can be predicted by introducing the PSE with or without the triaxiality term. Yang [48] provided a detailed explanation of the scatter characteristic of LCF life for precipitate-strengthened metallic alloys. It is noted that the grain interior exhibits higher LCF life compared with the micro-crack initiated at the inclusion, which all depends on its local stress state.…”
Section: Micromechanics Based Lcf Life Of Ufg Aa6061mentioning
confidence: 99%
“…The object of the present study is the Ni-based superalloy GH4169, which is frequently employed in aeroengine high-temperature structures. 34,35 Though many studies concerning the R-dependent FCG of the Ni-based superalloy exist, the R-effect at elevated temperatures still needs further investigation. 36,37 One of the most critical problems is identifying the R-effect and describing the Rdependent FCG at various temperatures.…”
Section: Introductionmentioning
confidence: 99%